The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/aud.0000000000001026
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Serological Prestin Levels in Humans and its Relation to Otoacoustic Emissions, a Functional Measure of Outer Hair Cells

Abstract: Objectives: Serological biomarkers, common to many areas of medicine, have the potential to inform on the health of the human body and to give early warning of risk of compromised function or illness before symptoms are experienced. Serological measurement of prestin, a motor protein uniquely produced and expressed in outer hair cells, has recently been identified as a potential biomarker to inform on the health of the cochlea. Before any test can be introduced into the clinical toolkit, the reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 72 publications
(94 reference statements)
2
15
1
Order By: Relevance
“…Previous reports suggested that EHF audiometry is generally better than standard audiometry and OAEs at detecting the early stages, i.e., small levels, of OHC loss 31 , 36 . Moreover, although we previously found a weak correlation between serum prestin levels and TEOAEs 15 , unlike serum prestin, TEOAEs did not correlate with noise exposure levels in the current study. Thus, either noise-related OHC damage is too small to be detected by audiometry and TEOAEs but can be detected by serum prestin levels, or low serum prestin levels in the At-Risk group is being driven by a factor other than OHC loss, as we consider next.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Previous reports suggested that EHF audiometry is generally better than standard audiometry and OAEs at detecting the early stages, i.e., small levels, of OHC loss 31 , 36 . Moreover, although we previously found a weak correlation between serum prestin levels and TEOAEs 15 , unlike serum prestin, TEOAEs did not correlate with noise exposure levels in the current study. Thus, either noise-related OHC damage is too small to be detected by audiometry and TEOAEs but can be detected by serum prestin levels, or low serum prestin levels in the At-Risk group is being driven by a factor other than OHC loss, as we consider next.…”
Section: Discussioncontrasting
confidence: 99%
“…That is, prestin may be removed from the inner ear as part of the normal proteomic recycling (turnover) processes that maintain cellular homeostasis. Consistent with this proposed homeostatic mechanism, we have previously shown that the healthy ear has stable levels of prestin molecules in circulation 15 . Possible mechanisms for uptake, recycling, and sorting of plasma-membrane proteins, such as prestin in the OHCs.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations